2002
DOI: 10.1046/j.0032-0862.2002.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule dynamics in compatible and incompatible interactions of soybean hypocotyl cells with Phytophthora sojae

Abstract: The arrangement of microtubules in soybean ( Glycine max ) cells was examined during compatible and incompatible interactions of hypocotyls of soybean cv. Harosoy (susceptible) and cv. Haro 1272 (resistant) with race 1 of the soybeanspecific pathogen Phytophthora sojae . Both reaction types were similar during the first 3 h after zoospore inoculation in terms of the number of cells penetrated, and depth penetrated into the cortex. By 3 h postinoculation, clear differences had developed between the two interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
0
27
1
Order By: Relevance
“…42,43 Microtubule organisation is also affected by defence responses, but the response is variable. Disruption and apparent depolymerisation of the microtubule network at the penetration site has been observed in several systems (Figure 1n), 39,40,44 and it has been suggested that this might be an early sign of the HR. 39,42 In other studies microtubules, like F-actin, concentrate at the infection site and undergo bundling, 42 but some studies 43 found no changes in the microtubule organisation upon pathogen attack.…”
Section: Involvement Of the Cytoskeleton In The Hypersensitive Responmentioning
confidence: 99%
“…42,43 Microtubule organisation is also affected by defence responses, but the response is variable. Disruption and apparent depolymerisation of the microtubule network at the penetration site has been observed in several systems (Figure 1n), 39,40,44 and it has been suggested that this might be an early sign of the HR. 39,42 In other studies microtubules, like F-actin, concentrate at the infection site and undergo bundling, 42 but some studies 43 found no changes in the microtubule organisation upon pathogen attack.…”
Section: Involvement Of the Cytoskeleton In The Hypersensitive Responmentioning
confidence: 99%
“…2, A and B). In barley-Erysiphe and flax-Melampsora interactions, radial arrays of microtubules form beneath the appressorium (Kobayashi et al, 1992(Kobayashi et al, , 1994, while in parsley (Petroselinum crispum)-or soybean (Glycine max)-Phytophthora sojae interactions, localized microtubule depolymerization has been observed (Gross et al, 1993;Cahill et al, 2002). In nonhost, incompatible, and compatible interactions of Arabidopsis with P. sojae or different races of Peronospora parasitica, there is neither focusing nor large-scale disappearance of microtubules at the infection site, although diffuse GFP-tubulin fluorescence and a circumferential alignment of microtubules across cell boundaries are observed around the penetration site (Takemoto et al, 2003).…”
Section: Plant Cytoskeletal Response To Pathogenic Fungi and Oomycetementioning
confidence: 99%
“…These interactions generally involve reorganization and/or focusing of the microtubule cytoskeleton around the infecting organism. However, rapid apparent depolymerization of microtubules has also been reported, for example, in parsley (Petroselinum crispum)-and soybean (Glycine max)-Phytophthora interactions and in elicitor-treated tobacco (Nicotiana tabacum) cells (Gross et al, 1993;Binet et al, 2001;Cahill et al, 2002). Nod factor signaling also stimulates rapid localized apparent depolymerization of microtubules in root hairs and later increases in microtubule arrays (Timmers et al, 1999;Weerasinghe et al, 2003).…”
Section: Signal-mediated Cortical Microtubule Reorganization/depolymementioning
confidence: 99%